KSHV manipulates Notch signaling by DLL4 and JAG1 to alter cell cycle genes in lymphatic endothelia. - Victoria Emuss; Dimitrios Lagos; Arnold Pizzey; Fiona Gratrix; Stephen R Henderson; Chris Boshoff (PLoS Pathogens)
Increased expression of Notch signaling pathway components is observed in Kaposi sarcoma (KS) but the mechanism underlying the manipulation of the canonical Notch pathway by the causative agent of KS, Kaposi sarcoma herpesvirus (KSHV), has not been fully elucidated. Here, we describe the mechanism through which KSHV directly modulates the expression of the Notch ligands JAG1 and DLL4 in lymphatic endothelial cells. Expression of KSHV-encoded vFLIP induces JAG1 through an NFkappaB-dependent mechanism, while vGPCR upregulates DLL4 through a mechanism dependent on ERK. Both vFLIP and vGPCR instigate functional Notch signalling through NOTCH4. Gene expression profiling showed that JAG1- or DLL4-stimulated signaling results in the suppression of genes associated with the cell cycle in adjacent lymphatic endothelial cells, indicating a role for Notch signaling in inducing cellular quiescence in these cells. Upregulation of JAG1 and DLL4 by KSHV could therefore alter the expression of cell cycle components in neighbouring uninfected cells during latent and lytic phases of viral infection, influencing cellular quiescence and plasticity. In addition, differences in signaling potency between these ligands suggest a possible complementary role for JAG1 and DLL4 in the context of KS.